Application of Customer Relationship Marketing Towards Customer Loyalty Through Trust in Bank - Angga Ade Permana; Muhammad Firdaus; Muhaimin Dimyati (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
Customer relationship marketing as a strategy to build good relationships with customers in the long run by combining the ability to respond directly and to serve customers with high interaction. The purpose of this study is whether customer relationship marketing influences customer loyalty through trust, directly or indirectly. The sampling technique that researchers took was Nonprobability sampling and using purposive sampling. The type of research method used in this research is path analysis, t-test, determination R2 . The path analysis results show that the variable component of customer relationship marketing which includes commitment and conflict handling has a significant direct relationship to trust and loyalty while communication does not have a negative influence or a negative effect on customer trust or loyalty